Cellular and transcriptomic changes by the supplementation of aged rat serum in human pluripotent stem cell-derived myogenic progenitors - Tey, Sin-Ruow; Anderson, Ryan S.; Yu, Clara H.; Robertson, Samantha; Kletzien, Heidi; Connor, Nadine P.; Tanaka, Kaori; Ohkawa, Yasuyuki; Suzuki, Masatoshi (Frontiers in Cell and Developmental Biology, 2024)
The changing composition of non-cell autonomous circulating factors in blood as humans age is believed to play a role in muscle mass and strength loss. The mechanisms through which these circulating factors act in age-related skeletal muscle changes is not fully understood. In this study, we used human myogenic progenitors derived from human pluripotent stem cells to study non-cellautonomous roles of circulating factors during the process of myogenic differentiation. By using serum samples from aged or young Fischer 344 × Brown Norway F1-hybrid rats, we first determined whether serum supplementation affected proliferation of myogenic progenitors prepared from human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs). We found that aged rat serum supplementation significantly reduced cell proliferation and increased cell death in both ESCand iPSC-derived myogenic progenitors. Next, we found that the supplementation of aged rat serum inhibited myotube formation and maturation during terminal differentiation from progenitors to skeletal myocytes when compared to the cells treated with young adult rat serum. Furthermore, we performed transcriptome analysis using serum supplemented myocytes and identified that gene expression profiles were affected following serum supplementation in culture. Together, aged serum supplementation caused cellular and transcriptomic changes in human myogenic progenitors. The current data from our in vitro model possibly simulate non-cell autonomous contributions of blood composition to age-related processes in human skeletal muscle.